2019
DOI: 10.4102/jef.v12i1.244
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between marital status and employment in South Africa

Abstract: Orientation: Marriage formalises gender roles in society and as such has a significant impact on the labour force. The institution does, however, change over time, which makes it important to continually assess the impact that it has.Research purpose: In this article, the impact of marital status on employment is gauged.Motivation for the study: Marriage is arguably one of the most engrained institutions in modern society. Understanding the link between the marriage institution and employment could be essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This article shows that there is a gender inequality in European labor market, where men's work hours are more than women's work hours which reflect the findings of some previous studies (e.g., (Bailyn, 1993;Coltrane, 1996;Janse van Rensburg et al, 2019;Kanji, 2013;Kitterød & Rønsen, 2012;Townsend, 2002;Vuong & Sid, 2020)) although some studies show that women's labor force participation is increasing in modern society (e.g., (Becker, 1985;Goldin, 1989;Mammen & Paxson, 2000;Olivetti, 2006;Tong & Chiu, 2017)). This article also finds that unmarried women work less hours than married women, although some of the previous studies argue marriage and maternity reduce the possibility of participating in the labor market (e.g., (Francis, 2011;Lee et al, 2008;Sasaki, 2002;Tong & Chiu, 2017)).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This article shows that there is a gender inequality in European labor market, where men's work hours are more than women's work hours which reflect the findings of some previous studies (e.g., (Bailyn, 1993;Coltrane, 1996;Janse van Rensburg et al, 2019;Kanji, 2013;Kitterød & Rønsen, 2012;Townsend, 2002;Vuong & Sid, 2020)) although some studies show that women's labor force participation is increasing in modern society (e.g., (Becker, 1985;Goldin, 1989;Mammen & Paxson, 2000;Olivetti, 2006;Tong & Chiu, 2017)). This article also finds that unmarried women work less hours than married women, although some of the previous studies argue marriage and maternity reduce the possibility of participating in the labor market (e.g., (Francis, 2011;Lee et al, 2008;Sasaki, 2002;Tong & Chiu, 2017)).…”
Section: Discussionsupporting
confidence: 84%
“…In the above discussion, we find that there are different views to explain the gender gap in employment hours. However, there is little discussion about the effects of marital status to the gender gap taking marital status as moderator, although there are some of the studies (e.g., (Boeckmann, Misra, & Budig, 2014;Janse van Rensburg, Claassen, & Fourie, 2019;Olivetti, 2006;Tumsarp & Pholphirul, 2020;Vijayakumar & Cunningham, 2019)) that focused on marital status. But these studies do not show the interaction between marital status, gender gap and employment hours.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that, while a significant positive effect on continuity in employment accrues for men who are married or who constitute a one-parent family, the opposite manifests for married women for whom a significant negative effect on employment is revealed. Such findings are echoed by Janse van Rensburg et al. (2019), who observed that married women are less likely to be employed, whereas men are more likely to be employed when they are married.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…This could be determined in association with housework costs, including childcare. Consequently, female partners who typically take charge of housework could be discouraged from improving human capital and labour participation in the marriage relationship compared to male partners, or single women who can independently decide human capital investment for the sake of employability (Becker, 1965; Borck, 2014; Chen et al, 2014; Grossbard-Schechtman & Neuman, 1988; van Rensburg, Claassen, & Fourie, 2019). Hence, work–family reconciliation policies which help females choose participation in the labour market could be equally helpful for female migrants.…”
Section: Previous Literaturementioning
confidence: 99%